Cadeias de Markov : uma conexão para conceitos de matrizes, probabilidades e grafos no ensino médio - Santos, Cristina Aparecida dos (2022)
Markov chains are stochastic processes that have a special property: the probability regarding what happens in the future depends only on what happens in the present. To approach them, it is necessary to start from the concepts of matrices and probabilities that are contents usually studied in the second year of high school. This work presents the Markov chains connecting these two contents to the study of graphs.